2017
DOI: 10.1017/s1463423617000688
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary validation of the physician support of skin self-examination scale

Abstract: Skin self-examination (SSE) is a crucial preventive health behaviour in melanoma survivors, as it facilitates early detection. Physician endorsement of SSE is important for the initiation and maintenance of this behaviour. This study focussed on the preliminary validation of a new nine-item measure assessing physician support of SSE in melanoma patients. English and French versions of this measure were administered to 188 patients diagnosed with melanoma in the context of a longitudinal study investigating pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Time since diagnosis and cancer stage were additionally collected from patients’ medical files and hospital tumour registries. The Physician Support of Skin Self-Examination Scale assessed the patients’ perspective of their doctors’ encouragement of skin self-examination (SSE) ( Coroiu et al, 2017 ). Patients’ self-efficacy for SSE was assessed using Skin Self-Examination Self-Efficacy Scale ( Bergeron et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Time since diagnosis and cancer stage were additionally collected from patients’ medical files and hospital tumour registries. The Physician Support of Skin Self-Examination Scale assessed the patients’ perspective of their doctors’ encouragement of skin self-examination (SSE) ( Coroiu et al, 2017 ). Patients’ self-efficacy for SSE was assessed using Skin Self-Examination Self-Efficacy Scale ( Bergeron et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, relationship satisfaction and quality, support of SSE by partners, partner motivation, and partner attendance at medical visits were positively associated with patients' self-efficacy to do SSE [27,30]. Physician support of SSE was associated with the intention to perform SSE [22,23]. Additionally, patients reported that routine education on how to do SSE helped them to identify thinner second primary melanomas [43].…”
Section: Factors Associated With Performing Sse Among Melanoma Survivors In Surveysmentioning
confidence: 98%
“…Twenty-five studies were conducted in the USA and five studies were carried out in Canada. Around one third of the studies were cross-sectional surveys (n = 12), nine of them were randomized controlled trials (RCTs), seven of them used a prospective research design, and the rest were qualitative using focus groups, (n = 1) [36] or analyzed secondary data (n = 1) [23].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations